Measuring the Public Value of a Land-Grant University - Courtney A. Meyers; Tracy A. Irani (Journal of Applied Communications, 2011)
Land-grant institutions are dependent on public funding to achieve their tripartite mission of teaching, research, and extension. This public support or the “public value” for land-grant institutions is crucial for the continued development and improvement of services and programs. The purpose of this study was to gather the perceptions and opinions of the University of Florida’s Institute of Food and Agricultural Sciences’ (IFAS) key stakeholders regarding its public value. The sample (N = 707) included community leaders and agricultural producers across the state. Nearly two-thirds had used IFAS programs or services and the majority reported being either very familiar or somewhat familiar with IFAS. Public value was measured using a constructed index. Results found that respondents who used IFAS programs or services provided a higher public value score than those who had not. Also, as respondents indicated higher levels of familiarity, the public value score increased. The type of respondent (i.e. producer or leader) was not a significant predictor of public value score. Overall, respondents indicated the most support for teaching, followed by research and extension. The results from this study provide justif ication for the continued support of IFAS programs and services. To ensure continued success, more must be done to encourage support for the three areas of IFAS among stakeholder groups. Future research should be conducted in other states to assess the public value of land-grant institutions and each component of the tripartite mission.
Keywords: Land-grant institutions; tripartite mission; FAS programs; lobally-ready graduates; stakeholders; research